Herb–drug interactions between Panax notoginseng or its biologically active compounds and therapeutic drugs: A comprehensive pharmacodynamic and pharmacokinetic review. (10th May 2023) - Xie, Yujuan; Wang, Changhong
Abstract: Ethnopharmacological relevance: Herbs, along with the use of herb–drug interactions (HDIs) to combat diseases, are increasing in popularity worldwide. HDIs have two effects: favorable interactions that tend to improve therapeutic outcomes and/or minimize the toxic effects of drugs, and unfavorable interactions aggravating the condition of patients. Panax notoginseng (Burk.) F.H. Chen is a medicinal plant that has long been commonly used in traditional Chinese medicine to reduce swelling, relieve pain, clear blood stasis, and stop bleeding. Numerous studies have demonstrated the existence of intricate pharmacodynamic (PD) and pharmacokinetic (PK) interactions between P. notoginseng and conventional drugs. However, these HDIs have not been systematically summarized. Aim of the review : To collect the available literature on the combined applications of P. notoginseng and drugs published from 2005 to 2022 and summarize the molecular mechanisms of interactions to circumvent the potential risks of combination therapy. Materials and methods: This work was conducted by searching PubMed, Scopus, Web of Science, and CNKI databases. The search terms included "notoginseng", "Sanqi", "drug interaction, " "synergy/synergistic", "combination/combine", "enzyme", "CYP", and "transporter". Results: P. notoginseng and its bioactive ingredients interact synergistically with numerous drugs, including anticancer, antiplatelet, and antimicrobial agents, to surmount drug resistance and side effects. This review elaborates on the molecular mechanisms of the PD processed involved. P. notoginseng shapes the PK processes of the absorption, distribution, metabolism, and excretion of other drugs by regulating metabolic enzymes and transporters, mainly cytochrome P450 enzymes and P-glycoprotein. This effect is a red flag for drugs with a narrow therapeutic window. Notably, amphipathic saponins in P. notoginseng act as auxiliary materials in drug delivery systems to enhance drug solubility and absorption and represent a new entry point for studying interactions. Conclusion: This article provides a comprehensive overview of HDIs by analyzing the results of the in vivo and in vitro studies on P. notoginseng and its bioactive components. The knowledge presented here offers a scientific guideline for investigating the clinical importance of combination therapies. Physicians and patients need information on possible interactions between P. notoginseng and other drugs, and this review can help them make scientific predictions regarding the consequences of combination treatments. Graphical abstract: Image 1 Highlights: Intricate pharmacodynamic and pharmacokinetic interactions often happen between P. notoginseng and conventional drugs. P. notoginsengcould reduce drug resistance and toxic side effects of anti-cancer drugs. Saponins in P. notoginseng could enhance anti-platelet drug activity and improve bleeding complications. P. notoginseng could sensitize numerous anti-microbial drugs. P. notoginseng could change the pharmacokinetic profiles of multiple therapeutic drugs.